Pengaruh Penilaian Kinerja terhadap Insentif Pada Pegawai Outsourcing PT Kereta Api Properti Manajemen (KAPM) area Palembang - Nizar, Muhammad Rafliansyah; Zunaidah, Zunaidah; Santati, Parama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to discover the effect of performance appraisal on incentive for outsourcing employee PT Kereta Api Properti Manajemen (KAPM) Palembang area. The population of the subject in this research are all outsourcing employees as the author sampling for 79 respondents. The method of data collecting used in this research is questioner. The analysis technique used in this research is simple linier regression analysis. Based on the result of the analysis, it can be concluded that performance appraisal had positive and significant effects on incentives for outsourcing employees PT Kereta Api Properti Manajemen (KAPM) area Palembang. Keywords: Performance Appraisal; Incentive